Sosialisasi dan Edukasi Sukuk bagi Pengurus Masjid Kementerian/Lembaga dan BUMN - Kusuma, Airlangga Surya; Faizi, Faizi; Widodo, Purwanto; Levianto, Jubei (Jurnal Pustaka Dianmas, 2025)
The sukuk market in Indonesia is still facing problems, even though Indonesia is a Muslim-majority country. One of the problems that hinders the development of the sukuk market is the poor understanding of sukuk. Therefore, training is needed to improve the community’s understanding of sukuk. To be more effective, the training should be aimed at parties that influence the community, such as mosque administrators. With this training, mosque administrators’ understanding of sukuk can be increased, and mosque administrators can pass on this understanding to a wider community. To carry out the training, the UPN Veteran Jakarta community service team collaborated with the Mosque Administrator Forum of Ministries/Institutions and SOEs to socialize sukuk for mosque administrators. The community service activity used a lecture method, followed by a discussion session. The result of this training is that mosque administrators have a better understanding of sukuk. Furthermore, mosque administrators should pass on knowledge about sukuk to the wider community.